Value-maximizing football clubs - Aloys Prinz; Stefan Thiem (Scottish Journal of Political Economy, 2021)
In this paper, football clubs are modeled as value-maximizing enterprises. With a long-term perspective in this framework, players are not only factors of production, but also assets of the club. It is shown that talent investment is higher with value-maximization than with profit maximization for homogeneous football clubs. Club heterogeneity is then modeled by different time-horizons regarding future profits, which leads to asymmetric levels of talent investment. Teams with longer time-horizons demand more talent and tilt the competition to their favor. Increases in transfer prices for players worsen the competitive balance, while higher player wages improve it.
Keywords: 330; football; players as assets; Tobin's q; value-maximization